2022
DOI: 10.3389/fnut.2021.794193
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Ligand Fishing Using Immobilized Cyclooxygenase-2 for Identification and Screening of Anticoronary Heart Disease Ligands From Choerospondias axillaris

Abstract: Inhibition of cyclooxygenase-2 (COX-2) activity is an effective way for treatment of coronary heart disease. And as an important source of COX-2 inhibitors, bioactive compounds of Choerospondias axillaris and pharmacological mechanisms remained lacking in prospective researches. Therefore, for the purpose of accelerating the discovery of natural products targeting designed inhibitors, the COX-2 microreactor composed of functionalized microspheres and magnetic ligand fishing was developed and applied in Choeros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Among the screened active ingredients, flavonoids (kaempferol, naringenin, and quercetin) in Choerospondias axillaris had high degrees of nodes, indicating the important role of total flavonoids in the treatment of PCH, which is consistent with previous research findings, According to reports, total flavonoids of GXST can alleviate cardiac dysfunction and myocardial interstitial fibrosis by regulating the NF-κB signaling pathway . Another study reported that it can inhibit cyclooxygenase-2 for the treatment of coronary heart disease . Diterpenoids (such as tanshinone iia and miltirone) in miltiorrhiza Bunge also had high node degrees and have been extensively studied in the field of cardiovascular disease (CVD) and served as reference standards for GXST .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the screened active ingredients, flavonoids (kaempferol, naringenin, and quercetin) in Choerospondias axillaris had high degrees of nodes, indicating the important role of total flavonoids in the treatment of PCH, which is consistent with previous research findings, According to reports, total flavonoids of GXST can alleviate cardiac dysfunction and myocardial interstitial fibrosis by regulating the NF-κB signaling pathway . Another study reported that it can inhibit cyclooxygenase-2 for the treatment of coronary heart disease . Diterpenoids (such as tanshinone iia and miltirone) in miltiorrhiza Bunge also had high node degrees and have been extensively studied in the field of cardiovascular disease (CVD) and served as reference standards for GXST .…”
Section: Discussionmentioning
confidence: 99%
“… 60 Another study reported that it can inhibit cyclooxygenase-2 for the treatment of coronary heart disease. 61 Diterpenoids (such as tanshinone iia and miltirone) in miltiorrhiza Bunge also had high node degrees and have been extensively studied in the field of cardiovascular disease (CVD) and served as reference standards for GXST. 62 Interestingly, some compounds, such as isorhamnetin, (+)-taxifolin, and isovitexin, were found in GXST but not in individual herbs.…”
Section: Discussionmentioning
confidence: 99%
“…The GO@Fe 3 O 4 @SiO 2 -NH 2 (SMGO-NH 2 ) nanoparticles were synthesized according to our previous work [ 38 ]. Based on the previous report, some modifications were made to coat PPAR-γ on the GO layer [ 39 ].…”
Section: Methodsmentioning
confidence: 99%